Adherence and the Moral Construction of the Self: A Narrative Analysis of Anticoagulant Medication. (December 2020) - Hawking, Meredith K. D.; Robson, John; Taylor, Stephanie J. C.; Swinglehurst, Deborah
In this article, we examine illness narratives to illuminate the discursive work that patients undertake to construct themselves as "good" and adherent. Biographical narrative interviews were undertaken with 17 patients receiving anticoagulation for stroke prevention in atrial fibrillation, from five English hospitals (May 2016–June 2017). Through pluralistic narrative analysis, we highlight the discursive tensions narrators face when sharing accounts of their medicine-taking. They undertake challenging linguistic and performative work to reconcile apparently paradoxical positions. We show how the adherent patient is co-constructed through dialogue at the intersection of discourses including authority of doctors, personal responsibility for health, scarcity of resources, and deservingness. We conclude that the notion of medication adherence places a hidden moral and discursive burden of treatment on patients which they must negotiate when invited into conversations about their medications. This discursive work reveals, constitutes, and upholds medicine-taking as a profoundly moral practice.